2009
DOI: 10.1080/03630240903238636
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Problems and Health Seeking in Sri Lanka

Abstract: Menstruation is associated with some morbidity, although it is a normal physiological event. In this article, we draw on qualitative research conducted in Sri Lanka in 2006-2007, which included eight key informant interviews with healthcare providers, six focus group discussions with eight women in each, and five case studies. We describe and analyze women's perceptions of menstruation and menstrual problems, their help-seeking behaviors to reduce these health problems, and the consequences of them on their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…In contrast, girls who had received information before menarche described more positive experiences. Where investigated, women and girls also lacked clarity on what constituted normal and abnormal (i.e., disordered) menstruation [47, 73, 85, 105, 109].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, girls who had received information before menarche described more positive experiences. Where investigated, women and girls also lacked clarity on what constituted normal and abnormal (i.e., disordered) menstruation [47, 73, 85, 105, 109].…”
Section: Resultsmentioning
confidence: 99%
“…In studies of those with dysmenorrhea or menstrual disorders, some participants were embarrassed to seek help. Others reported pursuing multiple avenues such as doctors and herbalists or community healers in attempts to receive effective treatment for their pain [103105, 109].…”
Section: Resultsmentioning
confidence: 99%
“…Women were associated with causes of this morbidity with curse, evil eye, watch craft, excessive body heat, and sterilization. Some women accept the problem as normal health ill of women; as a result, they do not seek care [42,43]. Certain untreated conditions can cause pregnancy related complications, congenital infections, infertility, chronic pain and significantly increase the risk of acquiring Pelvic Inflammatory Disease and HIV [41].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that many ailments suffered by older women in developing countries go untreated due to financial barriers in accessing health care, discrimination, unevenly distributed services between rural and urban areas, unfriendly treatment, and patriarchal decision-making processes (Ahmed et al, 2003;Hemachandra & Manderson, 2009;Hossen & Westhues, 2011;Kabir et al, 2003;Santow, 1995;Uzma, Underwood, Atkinson, & Thackrah, 1999). Studies have consistently shown that elders residing in rural areas have expressed a need for more accessible, equitable, and respectful health services (Hosain & Chatterjee, 1998;Hossen & Westhues, 2011;Reddy, 1996) and that women utilize modern health services less often than their male counterparts (Rahman, 2006).…”
mentioning
confidence: 99%